1996
DOI: 10.1200/jco.1996.14.5.1473
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of multiple courses of high-dose cyclophosphamide, thiotepa, and carboplatin for breast cancer or germ cell cancer.

Abstract: A sufficient number of PBPCs for two or three transplantations can be harvested from most patients without much difficulty before high-dose therapy. Two full-dose CTC courses or three tCTC courses can be given safely and with acceptable toxicity at 5-week intervals. Organ toxicity rather than bone marrow toxicity has become dose-limiting for alkylating agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 15 publications
0
55
0
Order By: Relevance
“…Toxicity of the high-dose CTC regimen JG Schrama et al (Rodenhuis et al, 1996). Patients who receive more than a single course of CTC may, however, develop major organ toxicity, including severe haemorrhagic cystitis, veno-occlusive disease and haemolytic uraemic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Toxicity of the high-dose CTC regimen JG Schrama et al (Rodenhuis et al, 1996). Patients who receive more than a single course of CTC may, however, develop major organ toxicity, including severe haemorrhagic cystitis, veno-occlusive disease and haemolytic uraemic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures of bone marrow harvesting and leucoytaphoris have been described previously (van der Wall et al, 1995;Rodenhuis et al, 1996Rodenhuis et al, , 1998Rodenhuis et al, , 1999Rodenhuis et al, , 2000.…”
Section: Treatment Regimenmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of peripheral blood haematopoietic progenitor cells (PBPCs) from different harvesting techniques and the possibilities of storage have raised interest in the administration of repetitive, closely spaced cycles of dose-intensive chemotherapy, each with PBPC rescue (Benjamin et al, 1995;Leyvraz et al, 1995;Pettengell et al, 1995;Vahdat et al, 1995;Rodenhuis et al, 1996). It was previously reported that autologous whole blood (without processing through a cell separator) 'primed' with chemotherapy and granulocyte colony-stimulating factor (G-CSF) provided sufficient PBPCs for myelosupportive effects (Pettengell et al, 1994(Pettengell et al, , 1995Preti et al, 1994;Ossenkoppele et al, 1996).…”
mentioning
confidence: 99%